Community Management of Herbicide‐Resistant Weeds in the Pacific Northwest. Issue 2 (10th March 2021) - Dentzman, Katherine
Abstract: While the threat of herbicide‐resistant (HR) weeds continues to grow, many of the known prevention and mitigation practices have not been widely adopted by farmers. Is lack of knowledge the reason? Studies have shown that farmers do in fact know what is needed to control HR weeds but nonetheless do not always use these practices. In talking with producers directly, researchers have found that they have many reasons for not adopting integrated weed management practices. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/846 .